ANALISIS DAYA SAING EKSPOR UDANG BEKU INDONESIA DI PASAR AMERIKA SERIKAT - Revan Wahyu Dimantara; Septina Elida (UIR Press, 2020)
ABSTRACT The United States is the main market for Indonesia's frozen shrimp exports, after Japan and the European Union. This study aims to analyze: (1) the export performance; (2) the export competitiveness; and (3) the factors affecting export of Indonesian frozen shrimp in the US market. This study uses library research methods, data analysis used in this study are: growth rate, concentration ratio (CR4) & Herfindahl Index (HI); Revealed Comparative Advantage (RCA) & Constant Market Share Analysis (CMSA); and linear regression with OLS estimation method. The results of the analysis show: (1) The growth of the export value of Indonesian frozen shrimp is 15.54%, while the value of CR4 & HI is 63,69% & 1.471, which are indicate that concentration and competition of the market is at moderate level, where Indonesia's market share is 15,21% (third highest after India and Thailand), (2) Indonesia's average RCA index is 20,11, the CMSA analysis show that the change in actual market share (0,77 x 10-4) is largely influenced by the competitiveness effect (98,74%), and the rest is influenced by the commodity composition effect (2,56%) and market distribution effect (-1,30%), (3) Factors that affect the export of Indonesian frozen shrimp in the US market significantly are domestic production, frozen shrimp export prices, processed shrimp export prices, and real exchange rates. Keyword: Competitiveness, Export, Frozen Shrimp, United States, HI, CR4, RCA, CMSA